Survival and Success Rates of Different Shoulder Designs: A Systematic Review of the Literature - Marco Tallarico; Marco Caneva; Silvio Mario Meloni; Erta Xhanari; Yuki Omori; Luigi Canullo (International Journal of Dentistry)
Objectives. To identify whether there is a relationship between different implant shoulder positions/orientations/designs and prosthetic and/or implant failures, biological or mechanical complications, radiographic marginal bone loss (MBL), peri-implant buccal recession (RC), aesthetic scores (Papilla Index, PES, and WES), and patient satisfaction after a minimum of 1 year function in the aesthetic zone, compared to the two-piece, conventional implant neck architecture. Materials and Methods. The systematic review was written according to the PRISMA guidelines. The search strategy encompassed the English literature from 1967 to September 2016 and was performed online (in the PubMed database of the U.S. National Library of Medicine, Embase, and the Cochrane Library) to identify relevant studies that met the inclusion criteria. The assessment of quality and risk of bias of the selected manuscripts was performed according to the guidelines provided by CONSORT and STROBE statements. Results. A total of 16 articles (7 randomized controlled trials, 4 observational comparative studies, and 5 systematic reviews) were selected to fulfill the inclusion criteria. A trend of higher implant failure and prosthetic complications were experienced in the one-piece group compared to the two-piece group, although no statistically significant differences were found. Higher marginal bone loss was found in the test group (one-piece, scalloped implants) compared to the control group (two-piece, flat implants). No comparative studies reporting data on sloped implants were found that fulfilled the inclusion and exclusion criteria of this systematic review. No differences were experienced between groups regarding aesthetic outcomes and patient satisfaction. Conclusions. There was sufficient evidence that different implant shoulder positions/orientations/designs (scalloped, sloped, and one piece) offer no benefit when compared to two-piece, conventional flat implants. Current evidence is limited due to the quality of available studies.